2021
DOI: 10.3991/ijim.v15i17.23731
|View full text |Cite
|
Sign up to set email alerts
|

The Acceptance of Mobile Learning: A Case Study of 3D Simulation Android App for Learning Physics

Abstract: This study investigates the adoption of the mobile learning, 3D simulation Android app, as an innovative tool for learning in physics for high school students. The factors affecting the acceptance of mobile learning are also determined in this study. The proposed research model employs two constructs, Perceived Usefulness and Perceived Ease of Use, from Technology Acceptance Model (TAM) as a baseline and adds another relevant factor based on prior mobile learning adoption research, Perceived Enjoyment. Data ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…Additionally, if ML as new innovative technology gives the students greater enjoyment in performing their learning activities, they intend to switch to using it. Several authors reported that perceived enjoyment strongly affects students’ intention to adopt ML systems (Pramana, 2018 ; Lisana & Suciadi, 2021 ). Conversely, a study by Rehman et al, ( 2016 ) found that the influence of perceived enjoyment on student behavioral intention was insignificant.…”
Section: Theoretical Model and Hypotheses Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, if ML as new innovative technology gives the students greater enjoyment in performing their learning activities, they intend to switch to using it. Several authors reported that perceived enjoyment strongly affects students’ intention to adopt ML systems (Pramana, 2018 ; Lisana & Suciadi, 2021 ). Conversely, a study by Rehman et al, ( 2016 ) found that the influence of perceived enjoyment on student behavioral intention was insignificant.…”
Section: Theoretical Model and Hypotheses Developmentmentioning
confidence: 99%
“…In this study, the network externalities factor is defined as the extent to which the perceived value of ML increases as the number of users grows (Lisana, 2021 ). It implies that the network’s behavior toward the ML platform positively correlates with students’ acceptance of the platform.…”
Section: Theoretical Model and Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…A comfortable online learning environment can be created by combining mobile technology, contextual learning strategies, and meaningful learning designs (Lisana & Suciadi, 2021;Papadakis & Kalogiannakis, 2019). For example, recent research indicates that the use of Android learning media on mobile devices can provide an effective means of establishing socially interactive and constructivist learning environments (Drolia et al, 2020;Nurhasanah et al, 2022;Papadakis et al, 2020).…”
Section: Introductionmentioning
confidence: 99%